Association of Healthy Lifestyle and Life Expectancy in Patients With Cardiometabolic Multimorbidity: A Prospective Cohort Study of UK Biobank - Cheng, Xunjie; Ouyang, Feiyun; Ma, Tianqi; Luo, Yi; Yin, Jinghua; Li, Jinchen; Zhang, Guogang; Bai, Yongping (Frontiers in Cardiovascular Medicine, 2022)
Background: The prevalence of cardiometabolic multimorbidity, which significantly increases the risk of mortality, is increasing globally. However, the role of healthy lifestyle in the secondary prevention of cardiometabolic multimorbidity is unclear. Methods: In total, 290,795 participants with CMM, which was defined as coexistence of at least two of hypertension (HTN), diabetes mellitus (DM), coronary heart disease (CHD), and stroke (ST), and those without these four diseases at baseline were derived from UK Biobank. The associations between specific CMM patterns and mortality, and that between healthy lifestyle (including physical activity, smoking, alcohol consumption, and vegetable and fruit consumption) and mortality in patients with specific CMM patterns were calculated using the flexible parametric Royston-Parmar proportion-hazard model. Hazard ratios (HRs) and corresponding 95% confidence intervals (CIs) were calculated. Results: During a median 12.3-year follow up period, 15,537 (5.3%) deaths occurred. Compared with participants without cardiometabolic diseases, the HRs for all-cause mortality were 1.54 (95% confidence interval [CI]: 1.30, 1.82) in participants with HTN+DM, 1.84 (95% CI: 1.59, 2.12) in those with HTN+CHD, 1.89 (95% CI: 1.46, 2.45) in those with HTN+ST, and 2.89 (95% CI: 2.28, 3.67) in those with HTN+DM+CHD. At the age of 45 years, non-current smoking was associated with an increase in life expectancy by 3.72, 6.95, 6.75, and 4.86 years for participants with HTN+DM, HTN+CHD, HTN+ST, and HTN+ DM+CHD, respectively. A corresponding increase by 2.03, 1.95, 2.99, and 1.88 years, respectively, was observed in participants with regular physical activity. Non-/moderate alcohol consumption and adequate fruit/vegetable consumption were not significantly associated with life expectancy in patients with specific CMM patterns. Conclusion: CMM was associated with an increased risk of mortality. Regular physical activity and non-current smoking can increase life expectancy in patients with specific CMM patterns.